Partisipasi Masyarakat dalam Program Pengembangan dan Pengelolaan Jaringan Irigasi di Daerah Irigasi Way Umpu Kabupaten Way Kanan - Ismail, Ronaldi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Problem faced by the government regarding Development and Management of Irrigation Network program is the implementation have many weakness, which look at the low participation. Including a sense of belonging is low to existing irrigation networks. Public already familiar with the system development from top to bottom (top down) and passive waiting for the program and existing orders. yhe aim of research is to analyze the form and level of society participation and to know what factors influence community participation in Development and Management of Irrigation Network program at Way Umpu Irrigation Area, Way Kanan regency. This research used quantitative descriptive analysis support with qualitative analysis. Based on this study, its found that the participation in form energy, money and material, dominant forms of community participation is energy, followed by donations of money and material donations. Overall level of public participation in Development and Management of Irrigation Network program at the third level of eight Arnstein participation ladder. its mean at informing level and degree of tokenism.Â